TEACHER EDUCATORS: FROM “THE HIDDEN PROFESSION” TO REVEALED PROFESSION - Sysoieva, Svitlana; Sokolova, Iryna (The Modern Higher Education Review, 2018)
Knowledge about the EU policy regarding teacher educators is of significant interest to both scholars and stakeholders of higher education. The authors of this paper have identified four key areas where the analysis of current trends and the formulation of relevant questions for discussion seem to be particularly important for those involved in teacher education and training. These are the development of our knowledge basis about the EU initiatives on teacher education in Europe, the EU policy regarding teacher educators, the challenges and new trends characterising the role of teacher educators in the initial education and the professional development. This study also concentrates on teacher educators’ status, their profile of core values and areas of competence that underpin teacher educators’ diverse and multifaceted roles. The paper uses literature review as a basis in identifying critical parameters for the EU policy analysis and its implementation to higher education sector. The European expert study made some very specific proposals for the definition of a teacher educators’ competence profile, making a distinction between first-order and second-order knowledge, skills and attitudes and defining key competence areas. Two key actions to support teacher educators in Member States are characterized: to develop an explicit profile of the competences required by teacher educators; to reinforce collaboration between all the key actors in all phases of teacher education.